ESTIMATION OF THE PREDICTIVE EFFECT OF BODY MASS INDEX-PERCENTILE ON SKELETAL MATURATION IN A NIGERIAN POPULATION. - Osaronse Aghimien; Osasumwen Aghimien-Osaronse (Nigerian Dental Association, 2023)
Objectives: To determine the predicting the effect of BMI-index percentile on the skeletal maturation of Nigerian children.  Design: A prospective cross-sectional study. Setting: This study was conducted in a tertiary health care facility in North-Central Nigeria. Participants: Children between the ages of 5-17 years consisting of 44 males and 30 females that presented in the Child Dental clinic over a period of eight months were recruited for the study. Main outcome measured: Skeletal maturation was assessed using the middle phalanx of the third finger (MP3) while the standard WHO growth chart specific for age (2-20 years) and gender was used for grading BMI-percentile. The unpaired t-test was used to compare mean chronological age of the stages of MP3 according to gender. Multinomial logistic regression used to determine the predictive effect of age, gender and BMI percentile on pubertal growth spurt. Results: The BMI-percentile had weak correlation with the pubertal growth spurt (r=0.089, p=0.448). Gender (p=0.004) and chronological age had significant (p<0.001) predictive effect on the skeletal maturation. A one-percentile increase in the BMI-percentile decreases the likelihood of healthy children to be in the peak-pubertal by 1.504 when compared to obese children (p=0.305).  Conclusions: This study showed that BMI-percentile is a weak predictor of skeletal maturation. However, obese children had a tendency towards advanced skeletal maturation than healthy participants. It is therefore suggested that orthodontists should consider early implementation of jaw modification treatments among obese children.